Lutas e práticas de resistência dos camponeses na Era Vargas (1930-1945) - Rossetto, Neuri Domingos (2003)
The subject of my dissertation is the social struggles and practices of resistance employed by peasants during the Vargas government (1930-1945), the effects of which have their origin and extended beyond that period, which came to be known as the Vargas Era. Working from an analysis of the scenario of economic and political transformations of the period and an interpretive mapping out of proposals, demands and projects, this study takes as its principal focus the way in which the agrarian question appeared on the agenda of the Vargas government and the question of the struggles and resistance practices which took place in relation to the laws and rights by which, among other means, the extension of labour rights to the rural world was sought. Consequently this dissertation indicates an inverse path to the perspective which designates that historic period as one in which the dominant impression is of a vacuum or of the invisibility of the struggles and resistance practices of the peasants in the Vargas Era. The postulation is that the antecedents and what follows in the wake of this period are fundamental for the comprehension of the persistence of an unjust agrarian structure up until today, and for the way in which conflicts, struggles and demands coming from the subordinate classes were always dislocated and delegitimized as political actions